ACUTE AND CHRONIC EFFECTS OF CHIOS MASTIC GUM ON BLOOD PRESSURE IN A RODENT MODEL OF 2-KIDNEY 1-CLIP HYPERTENSION. (June 2018) - Tzani, A.; Doulamis, I.; Konstantopoulos, P.; Pasiou, E.; Daskalopoulou, A.; Iliopoulos, D.; Georgiadis, I.; Kavantzas, N.; Kourkoulis, S.; Perrea, D.
Abstract : Objective: Chios mastic gum (CMG), a Greek plant resin, has been studied for its protective role against endothelial and vascular inflammation by suppressing oxidative stress and downregulating the expression of pro-inflammatory mediators. We sought to investigate the effect of CMG administration on blood pressure (BP) and hypertension-induced target organ damage. Design and method: 16-week-old male Wistar rats were allocated into 3 groups: Control group; 2-kidney, 1-clip (2K1C) group; CMG group which was treated with CMG (40 mg/kg body weight /day) for 2-weeks after the establishment of hypertension. Results: Acute CMG administration led to a decrease in systolic, diastolic and mean arterial BP (153 vs 188 mmHg, 108 vs 141 mmHg and 122 vs 156 mmHg for CMG and 2K1C groups, respectively), while these hemodynamic effects were sustained throughout the 2-week administration period (136 vs 194 mmHg, 100 vs 141 mmHg and 112 vs 159 mmHg for CMG and 2K1C groups, respectively. CMG also attenuated target organ damage as proposed by amelioration of biomechanical properties of the aorta –including cross-sectional area (CSA), aortic wall stiffness and thickness-, reversal of myocardial small vessel hypertrophy and maintenance of serum albumin levels. Furthermore, CMG administration was associated with decreased interleukin-6 (IL-6) and C-reactive protein (CRP) levels. The BP lowering effects of CMG are likely to be mediated by the decrease in renin serum levels. Regression analysis showed that the amelioration of organ damage was BP-lowering dependent and was not correlated with direct effects of renin or with its anti-inflammatory properties. Conclusions: Our results indicate an anti-hypertensive effect of CMG via down-regulation of renin excretion and suppression of the inflammatory cascade associated with alleviation of target organ damage. These observations provide substantial evidence for the potentially beneficial role of CMG in treating hypertension, yet clinical translation studies are further required.